2011
DOI: 10.3758/s13423-011-0116-7
|View full text |Cite
|
Sign up to set email alerts
|

Are there bilingual advantages on nonlinguistic interference tasks? Implications for the plasticity of executive control processes

Abstract: It has been proposed that the unique need for early bilinguals to manage multiple languages while their executive control mechanisms are developing might result in long-term cognitive advantages on inhibitory control processes that generalize beyond the language domain. We review the empirical data from the literature on nonlinguistic interference tasks to assess the validity of this proposed bilingual inhibitory control advantage. Our review of these findings reveals that the bilingual advantage on conflict r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

59
667
14
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 679 publications
(748 citation statements)
references
References 119 publications
(260 reference statements)
59
667
14
8
Order By: Relevance
“…Furthermore, Gathercole et al (2014) found no evidence of a bilingual advantage in children, adolescents (13-16 years) and adults (18-90 years) (see also Paap & Greenberg, 2013 for the Flanker task). In a recent review Hilchey and Klein (2011) found that although bilinguals tended to perform faster than monolinguals, the congruency effect was of similar magnitude. This led them to conclude that bilinguals "enjoy a general processing advantage that can be detected early developmentally and that persists throughout life… [but] places the locus of control not on inhibitory processes per se, but on a central executive system that has some capacity to regulate processing across a wide variety of task demands" (p., 654).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Gathercole et al (2014) found no evidence of a bilingual advantage in children, adolescents (13-16 years) and adults (18-90 years) (see also Paap & Greenberg, 2013 for the Flanker task). In a recent review Hilchey and Klein (2011) found that although bilinguals tended to perform faster than monolinguals, the congruency effect was of similar magnitude. This led them to conclude that bilinguals "enjoy a general processing advantage that can be detected early developmentally and that persists throughout life… [but] places the locus of control not on inhibitory processes per se, but on a central executive system that has some capacity to regulate processing across a wide variety of task demands" (p., 654).…”
Section: Introductionmentioning
confidence: 99%
“…It has been claimed that the bilingual advantage in inhibitory control is particularly elusive in young children (Hilchey & Klein, 2011). In their meta-analysis of 39 studies, Donnelly, Brooks, and Homer (2015) ascertained the existence of a moderate but statistically significant bilingual advantage overall on global reaction time and interference costs from conflict resolution tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Socio-economic status (SES) might have acted as a confound in some studies (as suggested by Hilchey & Klein, 2011). Socially advantaged 4-to 7-year-old children have been shown to perform faster than their age-matched peers in terms of accuracy and speed in a flanker task (Mezzacappa, 2004), and parental level of education has been shown to predict children's development of executive functions (Ardila, Rosselli, Matute, & Guajardo, 2005;Merz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilinguals exhibit differential neural activation particularly in the bilateral prefrontal cortex, ACC, and striatum (Petitto and Dunbar 2009;Rodríguez-Pujadas et al 2014). However, there has been much debate over whether these findings are specific to language or domain-general (Hilchey and Klein 2011). The impact of bilingualism on critical-analytic thinking is unknown.…”
Section: Language Exposure and Bilingualismmentioning
confidence: 99%